Three new species of Atkinsoniella (Hemiptera, Cicadellidae, Cicadellinae) from southwestern China - Yan Jiang; Xiao-Fei Yu; Mao-Fa Yang (ZooKeys)
Three new species of the genus Atkinsoniella (Hemiptera: Cicadellidae: Cicadellinae), A. chongqingana Jiang & Yang, A. likuni Jiang & Yang and A. biostiolum Jiang & Yang, sp. nov., collected from southwestern China, are described and illustrated. The two new species, A. chongqingana Jiang & Yang, sp. nov. and A. likuni Jiang & Yang, sp. nov., are similar to A. nigrominiatula (Jacobi, 1944), A. latior Young, 1986, A. limba Kuoh, 1991, A. dormana Li, 1992, A. divaricata Yang, Meng & Li, 2017, A. peaka Yang, Meng & Li, 2017, and A. zizhongi Jiang & Yang, 2022 in appearances, but can be distinguished from these species by the characteristic of aedeagus, paraphysis, and pygofer. Atkinsonella biostiolum Jiang & Yang, sp. nov. can be distinguished from all the known Atkinsoniella species by its special color and markings, as well as males having one ostiole in the center of the base of each subgenital plate. A key to Atkinsoniella species from China is provided.